An experimentally verified model for thermal microactuators including nonlinear material properties, vacuum, and intra-device heat conduction. (9th January 2017) - Colbert, Keegan; Naraghi, Mohammad; Boyd, James G
Abstract: This paper presents a model and computational method to predict the steady-state performance of thermal flexure microactuators at high input powers and various levels of partial vacuum. The model accounts for nonlinear temperature dependence of material properties, heat loss due to radiation, and intra-device heat transfer by conduction across an air gap. The model is validated by comparing the model predictions with the experimentally measured voltage, current, and displacement at standard conditions, prior to adjusting for partial vacuum. In order to understand the effect of nonlinearities on model reliability, the predictions of six additional hypothetical models are considered where (1) intra-device heat transfer is neglected, (2) radiation is neglected, (3) the thermal conductivity of silicon is assumed to be temperature-independent, (4) the thermal conductivity of air is assumed to be temperature-independent, (5) the electrical resistivity of silicon is assumed to be linear in temperature, and (6) the thermal expansion coefficient of silicon is assumed to be temperature-independent. All factors except radiation were shown to have a significant influence on the device performance especially at high input powers. The experimentally validated full model is then employed to predict the effect of reduced air pressure on the displacement and heat transfer properties of the actuator. This aspect of the study targets applications of thermal actuators in controlled environments such as space applications, actuators used for in situ micropositioning and tensile testing inside electron microscopy chambers, or actuators incorporated into the design of MEMS resonators. It was demonstrated that the maximum actuator displacement is not a linear function of reduced pressure and that it reaches a maximum at a certain partial vacuum level.